Synthesis, structural characterization and comparison of experimental and theoretical results by DFT level of molecular structures of 1,2,3-triazoles derived from 5-chloroisatin - Tribak, Zineb; Skalli, Mohammed; Senhaji, Omar; Kandri Rodi, Youssef (International Journal of Advanced Chemistry, 2017)
This work deals about the synthesis, NMR characterization and the density functional method (B3LYP) with the 6-31G basis set of 1, 3-dipolar cycloaddition reactions between the two azides as dipoles and propargylchloroisatin as dipolarophile. Furthermore, DFT calculations were used to study the nucleophile–electrophile interactions of the azides and dipolarophile and also the stability between the regioisomers comparing their energy. Our calculations are in a good agreement with the experimental findings.